2014
DOI: 10.1089/apc.2013.0366
|View full text |Cite
|
Sign up to set email alerts
|

Retention Strategies and Factors Associated with Missed Visits Among Low Income Women at Increased Risk of HIV Acquisition in the US (HPTN 064)

Abstract: Women at high-risk for HIV acquisition often face challenges that hinder their retention in HIV prevention trials. These same challenges may contribute to missed clinical care visits among HIV-infected women. This article, informed by the Gelberg-Andersen Behavioral Model for Vulnerable Populations, identifies factors associated with missed study visits and describes the multifaceted retention strategies used by study sites. HPTN 064 was a multisite, longitudinal HIV seroincidence study in 10 US communities. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
77
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(80 citation statements)
references
References 46 publications
(82 reference statements)
1
77
2
Order By: Relevance
“…For example, studies conducted in East Africa have suggested unemployment, lower income, transportation costs, and other poverty indicators as likely barriers to retention in HIV care (Asefa, Taha, Dejene, & Dube, 2013;Namusobya et al, 2013). Similar results elsewhere indicate that women are more likely to miss appointments (Edwards, Parrish, Frieson, Crawford, & Thornton, 2011;Mugavero et al, 2009), delay seeking care (Tobias et al, 2007), and have unmet HIV-related health-care needs (Haley et al, 2014). Moreover, qualitative findings suggest childcare, socioeconomic commitments, and health services access as major barriers to patient engagement in HIV care (Rao et al, 2013).…”
Section: Introductionmentioning
confidence: 75%
“…For example, studies conducted in East Africa have suggested unemployment, lower income, transportation costs, and other poverty indicators as likely barriers to retention in HIV care (Asefa, Taha, Dejene, & Dube, 2013;Namusobya et al, 2013). Similar results elsewhere indicate that women are more likely to miss appointments (Edwards, Parrish, Frieson, Crawford, & Thornton, 2011;Mugavero et al, 2009), delay seeking care (Tobias et al, 2007), and have unmet HIV-related health-care needs (Haley et al, 2014). Moreover, qualitative findings suggest childcare, socioeconomic commitments, and health services access as major barriers to patient engagement in HIV care (Rao et al, 2013).…”
Section: Introductionmentioning
confidence: 75%
“…At screening, a total of 3234 of these women (78.4%) reported unprotected sex with a male during the past 6 months (screened “positive”) and 2099 of these (64.9%) chose to participate in HPTN 064. Details on followup and retention are provided elsewhere 9,13 .…”
Section: Resultsmentioning
confidence: 99%
“…39,40 Some studies with single-sex populations have noted that poverty and housing instability reduce retention and ART adherence. 41,42 We maintain that the absence of these data has been mitigated by the fact that all patients under study were successfully engaged in care (a prerequisite for the NA-ACCORD) and had access to ART. Immune status of individuals at ART start was also included in adjusted models, accounting for complications due to late care initiation (i.e., low CD4 + count).…”
Section: Discussionmentioning
confidence: 99%